Transcriptome Analyses Reveal Lipid Metabolic Process in Liver Related to the Difference of Carcass Fat Content in Rainbow Trout (Oncorhynchus mykiss). (29th August 2016) - Hu, Guo; Gu, Wei; Sun, Peng; Bai, Qingli; Wang, Bingqian
Abstract : Excessive accumulation of carcass fat in farm animals, including fish, has a significant impact on meat quality and on the cost of feeding. Similar to farmed animals and humans, the liver can be considered one of the most important organs involved in lipid metabolism in rainbow trout ( Oncorhynchus mykiss ). RNA-seq based whole transcriptome sequencing was performed to liver tissue of rainbow trout with high and low carcass fat content in this study. In total 1, 694 differentially expressed transcripts were identified, including many genes involved in lipid metabolism, such as L-FABP, adiponectin, PPAR- α, PPAR- β, and IGFBP1a . Evidence presented in this study indicated that lipid metabolic process in liver may be related to the difference of carcass fat content. The relevance of PPAR- α and PPAR- β as molecular markers for fat storage in liver should be worthy of further investigation.